Dihydroartemisinin induces apoptosis and autophagy‐dependent cell death in cholangiocarcinoma through a DAPK1‐BECLIN1 pathway. Issue 12 (5th September 2018) - Thongchot, Suyanee; Vidoni, Chiara; Ferraresi, Alessandra; Loilome, Watcharin; Yongvanit, Puangrat; Namwat, Nisana; Isidoro, Ciro
Abstract : Cholangiocarcinoma (CCA) is a very aggressive cancer arising from the malignant transformation of cholangiocytes. Intrahepatic CCA is associated with reactive inflammation and intense fibrosis of the hepatobiliary tract. Dihydroartemisinin (DHA), the active compound found in Artemisia annua, has been shown to possess anti‐tumor activity in a variety of human cancers, including hepatoma. Here, we tested the ability of DHA to specifically kill CCA cells and have investigated the underlying mechanisms. DHA induced both apoptosis and autophagy‐dependent caspase‐independent cell death in many CCA cell lines, while being slightly toxic to immortalized cholangiocytes. DHA induced the expression of many apoptosis‐ and autophagy‐related genes in CCA cells. In particular, it greatly induced the expression of DAPK1, and reduced the interaction of BECLIN1 with BCL‐2 while promoting its interaction with PI3KC3. Genetic silencing of DAPK1 prevented DHA‐induced autophagy. Pharmacologic and genetic inhibition of BECLIN1 function prevented autophagy and cell death induced by DHA in CCA cells. These data unravel a novel pathway of DHA cancer toxicity and open the possibility to introduce DHA in the therapeutic regimen for the treatment of CCA.